Alkaline-earth Metal Complexes of N-Phosphonomethyl Glycine - Mallikarjun Rao, G.; Ramesh, P.; Ram, Kashi (Asian Journal of Chemistry, 2010)
The proton-ligand formation constants of N-phosphonomethyl glycine (NPMG) and the complexation equilibria of its corresponding binary and ternary chelates with alkaline-earth metal ions, viz., Mg(II), Ca(II) and Sr(II) inolving some other O—O, N—N, N—O—O and N—O donors like catechol (Cat), oxalic acid (Oxa), 5-sulphosalicylic acid (5SSA), 1,10-phenanthroline (Phen), 2,2´-bipyridyl (Bipy), iminodiacetic acid (imda), glycine (Gly) and β-alanine (Ala) have been determined potentiometrically at a constant temperature (30ºC) and ionic strength (0.10 M KNO3) in aqueous medium. In presence of all the other chelating agents, except Gly and Ala, NPMG behaves as a secondary ligand while in the presence of Gly and Ala, it coordinates simultaneously with all the above mentioned metal ions. The binary and ternary stability constants (log K1 and log K´T or log KT), the differences in stability constants (D.S.C.) of 1 : 1 : 1 ternary and 1 : 1 secondary metal complexes (Δ log K´ or Δ log K), the percentages of relative stabilization ([%R.S.]) values and the distribution of metal ions in different chelated species have been evaluated and discussed.